DEVELOPING WORK PLANNING SKILLS BASED ON THE PHILOSOPHY OF SUFFICIENCY ECONOMY THROUGH ACTIVITY-BASED LEARNING AMONG UPPER SECONDARY SCHOOL STUDENTS - Booncharoen ์ฺNarumon; Kampetch, Jaruwan; ๊Uttaman Achira (Journal of Educational Review Faculty of Education in MCU, 2025)
This action research aimed 1) to develop work planning skills based on the Philosophy of Sufficiency Economy (SEP) in upper secondary school students through activity-based learning, and 2) to study the results of developing work planning skills based on SEP in upper secondary school students who participated in the activity-based learning. This research was an action research study with a sample group of 20 upper secondary school students from Ratjavinit Bangkaepankhum School who voluntarily participated in the activities. The research instruments included: 1) activity-based learning activities designed to develop work planning skills based on the Philosophy of Sufficiency Economy, and 2) an assessment form for work planning skills based on the Philosophy of Sufficiency Economy. Data were analyzed using mean and standard deviation. The research findings revealed that 1) The developed activity-based learning activities could effectively develop work planning skills based on the Philosophy of Sufficiency Economy in upper secondary school students. The activities comprised four sequential steps: 1. Sufficiency leading to a plan, 2. Systematic planning, 3. Creative plan adjustment, and 4. Individual planning. 2) After participating in the activity-based learning activities, upper secondary school students demonstrated a high level of overall work planning skills based on the Philosophy of Sufficiency Economy.